The Effect of Perceived Service on Consumer Loyalty to Gojek Online Transportation - Alysha Fitra Farahdhiya (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This research aims to determine the influence of perceived service on consumer loyalty to Gojek online transportation. The number of respondents in this research was 325 people from all over Indonesia. A research study found that the things that were felt to influence consumer loyalty were sales promotions, perceived benefits, perceived services, and consumer satisfaction. This research uses a quantitative approach that uses primary data. The technique used in collecting data for this study is by collecting questionnaires online. Researchers use Structural Equation Modeling (SEM), processed with the Smart-PLS software tool, to test the model and estimate. This study has limitations, the sample of respondents in this study is limited to young individuals aged between 23 and 27 years who are currently self-employed. Further research can analyze changes in the behavior patterns of older people who think carefully about the transportation used daily in their activities.